Model for Evaluating Employee Engagement in a Matrix Organization - Dávila Navarro, Joaquín G. (2023)
The objective of this project is to implement a model for evaluating employee engagement in a company through mobile and web applications that allow for measuring employee engagement in work teams. The proposed model is defined by seven stages: input, plan, organize, timeline, evaluate, monitor, and output. It also includes the tools, variables, and factors that affect the model. Furthermore, experts in the field evaluated the model using a questionnaire developed to determine its effectiveness. Ultimately, the model received a score of 4.56 out of 5 points for approval and usability in companies, and a continuity plan for future projects is provided.